From the ERM to the euro: new evidence on economic and policy convergence among EU countries - Ignazio Angeloni; Luca Dedola (European Central Bank (ECB), 1999)
Skeptic views on EMU are usually cast around three arguments. First, the EU does not satisfy 'Optimum Currency Area' (OCA) conditions. Second, heterogeneous economic and financial structures will produce differences in monetary transmission. Third, the shift from domestic to area-wide considerations may give rise to conflicts in the decision making of the European Central Bank (ECB).
Keywords: E52; F02; E32; 330; economic and policy convergence